Video-assisted functional assessment of index pollicisation in congenital anomalies. (August 2016) - Mas, Virginie; Ilharreborde, Brice; Mallet, Cindy; Mazda, Keyvan; Simon, Anne-Laure; Jehanno, Pascal
Purpose: Functional results of index pollicisation are usually assessed by the clinical score of Percival. This score is based on elementary hand movements and does not reflect the function of the neo thumb in daily life activities. The aim of this study was to develop a new video-assisted scoring system based on daily life activities to assess index pollicisation functional outcomes. Methods: Twenty-two consecutive children, operated between 1998 and 2012, were examined with a mean of 77 months after surgery. The mean age at surgery was 34 months. Post-operative results were evaluated by a new video-assisted 14-point scoring system consisting of seven basic tasks that are frequently used in daily activities. The series of tasks was performed both on the request of the examiner and in real-life conditions with the use of a hidden camera. Each video recording was examined by three different examiners. Each examiner rated the video recordings three times, with an interval of one week between examinations. Inter- and intra-observer agreements were calculated. Results: Inter- and intra-observer agreements were excellent both on request (κ = 0.87 [0.84–0.97] for inter-observer agreement and 0.92 [0.82–0.98] for intra-observer agreement) and on hidden camera (κ = 0.83 [0.78–0.91] for inter-observer agreement and 0.89 [0.83–0.96] for intra-observer agreement). The results were significantly better on request than on hidden camera ( p = 0.045). The correlation between the video-assisted scoring system and the Percival score was poor. Conclusion: The video-assisted scoring system is a reliable tool to assess index pollicisation functional outcomes. The scoring system on hidden camera is more representative of the neo thumb use in daily life complex movements. Level of evidence: Level IV.